Manejo de resíduos de laboratórios químicos em universidades - estudo de caso do departamento de química da UFSCar - Sassiotto, Maria Lucia Passarelli (Universidade Federal de São Carlos, 2005)
The universities have a basic role in a formation of a citizen, in other words, they are centers of science, technology and knowledge that affect all the society. However, the universities, through their activities of research, learning and extension, ending up by generating wastes potentially hazardous, such as the chemical laboratories. However they cannot more delay anymore the solution of this problem. This research task was elaborated with the aim of presenting a study about the chemical wastes handling potentially hazardous in the universities campi, with the study of the Chemistry Department (CD) of the Universidade Federal de São Carlos. Through visits to other institutions in order to know their experiences with the management of chemical wastes and, on the basis of the survey of passive and active of the wastes in the chemical laboratories of CD, proposals to the management to these problems can be elaborated. These proposals are based on the prevention and in the corrective control. The preventive focus, primary, aims the survey of techniques and actions to reduce the generating sources (chemical laboratories of education and research). The corrective control aims the treatment and posterior disposal of the generated wastes. As conclusions, it is aimed to subsidize the implantation of a program of management of the hazardous wastes in the UFSCar, aiming to reduce their environment impacts.
Keywords: Resíduos perigosos; Laboratórios químicos - medidas de segurança; Gerenciamento de resíduos; Resíduos gerados em universidades; Minimização de resíduos químicos; Laboratory waste; Hazardous waste; Laboratory waste management; University waste; ENGENHARIAS::ENGENHARIA CIVIL